Leadership Style on Organizational Culture and Good Corporate Governance - Ida Ayu Nyoman Yuliastuti; Daniel Raditya Tandio (AIBPM Publisher, 2020)
This study aims to determine the mediating effect of organizational culture variables between leadership style and Good Corporate Governance (GCG) in the Village Credit Institution (LPD) in Gianyar Regency. The sample used was 73 LPD of Gianyar Regency. The analysis technique used is Partial Least Square (PLS). The analysis shows that organizational culture provides a partial mediation effect on relationship between charismatic leadership styles and GCG, while in the relationship between transformational leadership styles and GCG, organizational culture provide full mediation. The implication of this research is that a good organizational culture of the institution will improve GCG in the institution.